Improving the Coaching Knowledge of Physical and Sports Teachers to Improve Students Sports Achievements in Malang City - Sugiyanto; Eko Hariyanto; Arief Darmawan; Ahadi Priyohutomo; Cahyo Nugroho Sigit (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Ideally physical education teachers have three main competencies in supporting student development. First, the ability to develop movement activities that aim to facilitate physical activity and maintain the health of students through an educational approach. Second, skills in developing non-academic achievements according to the talents and interests of students, both inside and outside the school environment. Third, the ability to develop and optimize the potential for student achievement in sports. Opportunities for students who have talent and ability in sports are increasingly open with the existence of various championship events at the regional and national levels. However, these opportunities are often not balanced with an increase in the coaching science competencies possessed by physical education teachers. Community service method uses the lecture method, mentoring, and measurement of results. Results of this community service explain that teachers are aware of the importance of developing a structured and effective training program, but they face obstacles such as limited sports facilities in schools and minimal knowledge of sports psychology. In addition, they also pay less attention to continuous evaluation in training and tend to use conventional training techniques. Therefore, this community service emphasizes the importance of advanced training to update their knowledge, as well as the need for a more flexible training approach that is tailored to the needs of individual students.